Praktikum za kazensko materialno pravo: Z repetitorijem za študente - Šepec, Miha; Cvikl, Lana; Zgaga Markelj, Sabina (University of Maribor Press, 2026)
Practical Coursebook for Substantive Criminal Law: With Revision Guidebook for Students. The practical coursebook for substantive criminal law is a necessary tool for faculty tutorials. In addition to many practical examples, through which students receive a detailed insight into the key institutes of criminal law, it also includes an extensive and detailed revision guidebook, which is a teaching-of-theory tool for students. The guidebook also includes an overview of all novelties introduced to the Criminal Code with its’ latest amendment. The chapter "Method to solving a complex criminal case", provides additional value, as it offers students a detailed explanation of the procedure they must follow, to successfully solve a more complex practical criminal case (which often causes them great problems at their exam). This coursebook will be used for tutorials in all criminal law courses at the Faculty of Criminal Justice and Security.